2010
DOI: 10.1590/s0004-282x2010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Auditory evoked potentials and multiple sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory, demyelinating disease that can affect several areas of the central nervous system. Damage along the auditory pathway can alter its integrity significantly. Therefore, it is important to investigate the auditory pathway, from the brainstem to the cortex, in individuals with MS. Objective: The aim of this study was to characterize auditory evoked potentials in adults with MS of the remittent-recurrent type. Method: The study comprised 25 individuals with MS, between 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 18 publications
3
34
0
2
Order By: Relevance
“…They are closely related to abnormalities found in late AEP, especially latency delay of the P300 wave (Matas et al, 2010). It occurs at about 300 ms latency from the stimulus onset in young adults, with larger amplitude over the central-parietal scalp regions.…”
Section: Speech Intelligibilitymentioning
confidence: 70%
See 1 more Smart Citation
“…They are closely related to abnormalities found in late AEP, especially latency delay of the P300 wave (Matas et al, 2010). It occurs at about 300 ms latency from the stimulus onset in young adults, with larger amplitude over the central-parietal scalp regions.…”
Section: Speech Intelligibilitymentioning
confidence: 70%
“…Moreover, many studies indicate a significant correlation between auditory P300 latency and crucial demyelinating Levine at al., 1993b. ) plaques seen in MRI on frontal horn and brainstem (Honig et al, 1992;Sailer et al, 2001;Magnano et al, 2006;Matas et al, 2010).…”
Section: Speech Intelligibilitymentioning
confidence: 99%
“…BAEP consists of seven waves generated by one of the structures along the auditory pathway, while AMLR consists of a series of waves that appear after the BAEP and reflect the activation of several subcortical structures. Compared with healthy individuals, patients with relapsing-remitting MS have higher values for latencies of waves III and V and interpeaks I-III and I-V [58]. The same study showed no differences between MS patients and healthy controls for either latency of wave Pa or Na-Pa amplitude of AMLR [58].…”
Section: Auditory Epsmentioning
confidence: 77%
“…Chronic MS patients have been shown to have abnormalities in auditory evoked potentials, indicating dysfunction of different regions of the central auditory nervous system [5]. Optic pathway involvement in MS is frequently the initial sign in the disease process [6].…”
Section: Introductionmentioning
confidence: 99%